20-Gbit/s direct modulation of GaInAsP/InP membrane distributed-reflector laser with energy cost of less than 100 fJ/bit. (19th December 2017) - Tomiyasu, Takahiro; Inoue, Daisuke; Hiratani, Takuo; Fukuda, Kai; Nakamura, Nagisa; Uryu, Tatsuya; Amemiya, Tomohiro; Nishiyama, Nobuhiko; Arai, Shigehisa
Abstract: We demonstrated 20-Gbit/s direct modulation with a low energy cost of the membrane distributed-reflector (DR) laser whose static lasing characteristics were previously reported by Tomiyasu et al. inAppl. Phy. Express10, 062702 (2017) . As a small-signal modulation characteristic, a modulation current efficiency of 12 GHz/mA 1/2 was obtained. In 20-Gbit/s direct modulation using a non-return-to-zero 2 11 − 1 word-length pseudorandom bit sequence signal, a clear eye opening with a bit-error rate of 6.4 × 10 −10 was obtained with a bias current of 1.06 mA and a bias voltage of 1.76 V, which resulted in a record low energy cost of 93 fJ/bit among membrane distributed-feedback (DFB) and DR lasers ever reported.